A pilot randomized double-blind, placebo-controlled study on the effects of the topical application of pyridoxine on palmar-plantar erythrodysesthesia (PPE) induced by capecitabine or pegylated liposomal doxorubicin (PLD) - Charalambous, Andreas; Tsitsi, Theologia; Astras, George; Paikousis, Lefkios; Filippou, Elena (My University, 2021)
Purpose: Palmar-Plantar Erythrodysesthesia (PPE) is a dose-limiting adverse event that commonly occurs with capecitabine and Pegylated Liposomal Doxorubicin-PLD treatment. The study aimed to test the effectiveness of a Pyridoxine (B6) treatment protocol in the management of PPE in patients receiving treatment with capecitabine or pegylated liposomal doxorubicin. Methods: This was a pilot randomized double-blind, placebo-controlled study. Patients receiving capecitabine or pegylated liposomal doxorubicin with PPE grade 1 or above were randomly allocated to receive pyridoxine or placebo. The PPE grade, Quality of Life-QoL, Pain and patients’ activities of daily living were assessed. Results: Thirty patients were assigned in the Control and 24 in the Intervention group. No statistically significant difference was found in the PPE grade between baseline and week 6 in the 2 groups (p = 0.263). The control group exhibited worst PPE-associated QoL and higher PAIN levels between baseline and week 6. Respectively, the intervention group showed improved PPE-associated QoL and lower PAIN levels. At week 6, the ECOG status in the Intervention group was improved compared to the control (p = 0.018). Patients in the Intervention group experienced better Global Health Status (p = 0.012), Physical (p = 0.003), Emotional (p = 0.008), and Social function (p < 0.001), lower Fatigue (p = 0.001) and Pain (p = 0.006) compared to Control. Conclusion: Topical pyridoxine was not shown to have an effect on the treatment of PPE. However, results demonstrated its effectiveness on health related QoL, QoL-associated with PPE and pain levels. Due to the high attrition rate further validation of these results in a larger population is warranted. ClinicalTrials.gov identifier: NCT02625415.
Keywords: Capecitabine; Hand-foot syndrome; Palmar-plantar erythrodysesthesia; Pegylated liposomal doxorubicin; Quality of life; Symptom management